2020
DOI: 10.1099/jgv.0.001447
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of the avian virome

Abstract: The last two decades have seen the rise of viromics, the study of viral communities through the detection and characterization of virus genome sequences. Here we systematically review and summarize the scope and limitations of our current understanding of avian viromes, in both domesticated and wild-bird populations. We compare this viromic work to the broader literature on avian prokaryotic microbiomes, and highlight the growing importance of structured sampling and experimental design for testing explanatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…As in many recent avian virome studies, most of the newly identified viruses were from the families Picornaviridae , Parvoviridae , Circoviridae , and Caliciviridae [ 40 ]. Generally, all the closest relatives of the viruses discovered in this study were avian viruses, indicative of a relatively long evolutionary history in birds.…”
Section: Discussionmentioning
confidence: 99%
“…As in many recent avian virome studies, most of the newly identified viruses were from the families Picornaviridae , Parvoviridae , Circoviridae , and Caliciviridae [ 40 ]. Generally, all the closest relatives of the viruses discovered in this study were avian viruses, indicative of a relatively long evolutionary history in birds.…”
Section: Discussionmentioning
confidence: 99%
“…Research based on other molecular techniques would be advisable for better understanding of the real role of the viruses mentioned in this paper. A promising alternative could be viral metagenomics (viromics), which is based on the unbiased amplification of genetic material rather than the amplification of conserved genes that are not shared by all viruses, allowing the simultaneous detection of all the members of viral communities (thus the detection of co-infections), and putatively to the discovery of new viral agents responsible for watery droppings [114].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a need to clearly identify the gaps in our modern understanding of wild bird and poultry viromes. Avian viromes can generate additional information to routine monitoring programs and clarify our understanding of how zoonotic viruses effect human health [14,15]. Currently, with the widespread development of technologies for next generation sequencing (NGS) and the analysis of metagenomic data, more and more information on microbial communities is becoming available to researchers.…”
Section: Perspectives Of the "Avian Pathogens" Researchmentioning
confidence: 99%